Comparison of the Effectiveness of Unified Transdiagnostic Treatment and Short-Term Psychodynamic Therapy on the Spiritual Health of Women Affected by Marital Infidelity - Zahra Karimi; Ghamari, Mohammad; Hosseinian, Simin (Psychology of Woman Journal, 2024)
Objective: The present study aimed to compare the effectiveness of unified transdiagnostic and short-term psychodynamic treatments on the spiritual health of women affected by marital infidelity. Methods and Materials: A quasi-experimental design using a pretest-posttest-follow-up with a control group was employed. The population included women affected by marital infidelity in Jam city during the first six months of 2022, and the sample consisted of 45 eligible and volunteering individuals who approached a social studies counseling center. These women were initially assessed and selected for the pretest, then randomly assigned to two experimental groups and one control group (15 per group). The short-term psychodynamic group received 12 sessions and the unified transdiagnostic group underwent 8 sessions of individual therapy, while the control group was placed on a waiting list. After the treatment sessions, a posttest and a two-month follow-up test were conducted. The Spiritual Well-Being Scale by Paloutzian and Ellison (1982) was used, along with multivariate analysis of covariance and SPSS software version 26 to test the hypotheses. Findings: Both treatments were effective in enhancing the spiritual health of women, with the unified transdiagnostic treatment being more effective compared to the short-term psychodynamic therapy, and this effectiveness was sustained over time. (P<.05) Conclusion: Given the effectiveness and the differences in the impacts of unified transdiagnostic and short-term psychodynamic treatments on the spiritual health of women affected by marital infidelity, it is recommended that these treatments be considered in their counseling.